Natural convection in a horizontal cylindrical annulus filled with a porous medium saturated by a nanofluid using Tiwari and Das’ nanofluid model; The European Physical Journal Plus; Vol. 53 - Sheremet M. A. Mikhail Aleksandrovich (2015, 2015)
Title screen